2014
DOI: 10.1508/cytologia.79.85
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxic Risks Due to Temporal Changes in Soil Urea: Using <i>Allium cepa</i> L. Root Tip Bioassay

Abstract: Summary Breakdown of soil urea yields ammonium ions or ammonia, which further converts to nitrite and nitrate due to nitrification. These breakdown products have severe toxic effects on the crop standing in the soil when present in high concentrations. Temporal changes in ammoniumnitrate ratio following urea application in soil and its consequent genotoxic effects were assessed. In an in vitro experiment, a treatment of different concentrations of urea was given to Allium cepa bulbs for different durations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Urea exhibited a direct mutagenic effect on postmeiotic stages, whereas ammonium nitrate and calcium nitrate revealed an indirect mutagenic effect on meiotic and pre-meiotic stages in Drosophila melanogaster, as reported by El-Din et al (2009). This study showed that the tested nitrogenous fertilizers possesses mutagenic potentialities which are related to their nitrogen content, as also reported by Arora et al (2014) with AT.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Tisupporting
confidence: 77%
See 1 more Smart Citation
“…Urea exhibited a direct mutagenic effect on postmeiotic stages, whereas ammonium nitrate and calcium nitrate revealed an indirect mutagenic effect on meiotic and pre-meiotic stages in Drosophila melanogaster, as reported by El-Din et al (2009). This study showed that the tested nitrogenous fertilizers possesses mutagenic potentialities which are related to their nitrogen content, as also reported by Arora et al (2014) with AT.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Tisupporting
confidence: 77%
“…These breakdown products have severe toxic effects on the crop standing in the soil, when present in high concentrations. Treatment of different concentrations of urea was given to Allium cepa bulbs for different durations and variation was observed in the percentage of MI and percentage of anomalous cells during the span of the experiment by Arora et al (2014). Two distinct types of abnormalities were observed: (i) mitotic abnormalities, i.e.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Timentioning
confidence: 99%
“…There were more interphase nuclear anomalies for urea in the second WAT, indicating that prolonged treatment was not conducive for cell division (Figure 4(b)). The reason could be disturbance in the ratio of NH 4 + and NO 3 in soil (Arora et al 2014). The indiscriminate use of N fertilizers (disturbed balance of NH 4 + and NO 3 -) may induce array of chromosomal variations in the plant systems which may impose genotoxic risks.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have stated that excessive nitrogen fertilization can diminish soil fertility by reducing microbial enzymes and causing cytogenotoxicity (ARORA et al, 2014;SRIVASTAVA, 2017). According to Verma and Srivastava (2017), nitrogen-based fertilizers can cause chromosomal damage, cytological changes and other abnormalities during Allium cepa cell division.…”
Section: Cytotoxic and Genotoxic Analysismentioning
confidence: 99%